AN IDENTIFICATION KEY FOR THE FRESHWATER SHRIMPS OF KEPULAUAN BANGGAI, SULAWESI TENGAH - Arifqa, Hiqma; Tadeko, Fazlur Rahman I; Annawaty (Biocelebes, 2025)
This study developed a key for identifying freshwater shrimp species collected from the Banggai Islands, Central Sulawesi, Indonesia. Such keys are essential tools for biodiversity studies and species identification, benefiting researchers, students, and institutions. Conducted between October 2023 and April 2024 at the Laboratory of Animal Biosystematics and Evolution (BSHE), the research utilized existing specimens from the Banggai Islands previously deposited and stored within the BSHE collection. Methodology comprised specimen sorting, sexing, photographic documentation, taxonomic identification, and subsequent construction of the dichotomous key. The resulting key encompasses two species within the family Atyidae (Caridina brevicarpalis and C. typus) and four species within the family Palaemonidae (Macrobrachium australe, M. equidens, M. lar, and M. latidactylus).